Experimental and numerical analysis of hot deformation during press forming of Ti-6Al-4V alloy for aerospace applications - Uz, Murat Mert; Yapici, Guney Guven; Yoruc, Afife Binnaz Hazar; Aydogan, Cahit Sertac (KOREAN SOC MECHANICAL ENGINEERS, 2025)
In this study, hot press forming of an aero-structural Ti-6Al-4V sheet was examined by experimental and numerical simulation. The effects of hot forming parameters were examined in experiments performed at 700 degrees C and 800 degrees C forming temperatures, 0.5 mm/s and 2 mm/s intervals, different press tonnages and holding times. Stress and equivalent plastic strain distributions and shell thickness changes during forming were estimated with finite element analysis in ABAQUS-CAE software. According to the results, it was seen that the most significant effect on formability among the forming parameters was temperature, and the forming tonnage and holding time were also effective. With the finite element model created, the material behavior could be predicted numerically with high accuracy.
Keywords: Ti-6Al-4V alloy; Hot forming; Finite element analysis; Microstructure; Formability; Aerospace; BEHAVIOR; Engineering